2021
DOI: 10.1371/journal.pone.0261698
|View full text |Cite
|
Sign up to set email alerts
|

DAVS-NET: Dense Aggregation Vessel Segmentation Network for retinal vasculature detection in fundus images

Abstract: In this era, deep learning-based medical image analysis has become a reliable source in assisting medical practitioners for various retinal disease diagnosis like hypertension, diabetic retinopathy (DR), arteriosclerosis glaucoma, and macular edema etc. Among these retinal diseases, DR can lead to vision detachment in diabetic patients which cause swelling of these retinal blood vessels or even can create new vessels. This creation or the new vessels and swelling can be analyzed as biomarker for screening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A total of 300 images of ROP Stage III were correctly classified by both the ophthalmologist and the algorithm to be of poor quality, while two (2) images of ROP Stage III were classified by the ophthalmologist to be of quality, but the algorithm classified them as of non-quality. Studies applying morphological operations for retina image quality assessment were divided into three categories: Image vessel extraction and feature extraction to determine available features [14], [15], [21], quality assessment studies based on assigned values [16,18,19,22,24] and image contents with edge detection [17], [20], [25]. It is observable that all studies evaluated image quality based on some parameters of image contents which constituted the available features without paying more focus on image clarity which our algorithm was able to do.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 300 images of ROP Stage III were correctly classified by both the ophthalmologist and the algorithm to be of poor quality, while two (2) images of ROP Stage III were classified by the ophthalmologist to be of quality, but the algorithm classified them as of non-quality. Studies applying morphological operations for retina image quality assessment were divided into three categories: Image vessel extraction and feature extraction to determine available features [14], [15], [21], quality assessment studies based on assigned values [16,18,19,22,24] and image contents with edge detection [17], [20], [25]. It is observable that all studies evaluated image quality based on some parameters of image contents which constituted the available features without paying more focus on image clarity which our algorithm was able to do.…”
Section: Resultsmentioning
confidence: 99%
“…Anisotropic approach was used to normalize arrays for the vessels achieving an accuracy of 95%. Raza et al [19] developed an algorithm to check image content and reduce image noise for vessel visibility. This method was effective in detecting image edges through a developed image frame.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between AA, VA, age, systolic blood pressure (SBP), and diastolic blood pressure were carefully observed. Authors in [16] have suggested a Dense Accumulation Vessel Segmentation Network (DAVS-Net), which can provide good segmentation accuracy with only a few trainable parameters. This network employs an encoderdecoder framework, where edge information is passed from the initial layers of the encoder to the final layer of the decoder, in order to achieve faster convergence.…”
Section: Hypertensive Retinopathymentioning
confidence: 99%
“…Deep-learning-based techniques have shown very promising results when it comes to detecting complex patterns in a wide variety of medical images generally including those in retinal fundus images [17][18][19]. Numerous procedures to segment retinal blood vessels automatically from digital fundus images have been presented in the literature [20].…”
Section: Introductionmentioning
confidence: 99%